Adolescent Coping Strategies with Parental Divorce: A Narrative Review - Iyus Yosep; Ai Mardhiyah; Rohman Hikmat (Science Midwifery, 2022)
Parental divorce is one of the long-term stresors in children that can have negative impacts such as difficulty in building relationships, communicating, often feeling anxious, and irritable. So that adaptive coping is needed in dealing with these stresors. There are two coping strategies, namely emotional-focused coping and problem-focused coping, as well as adaptive and maladaptive categories. Therefore, the purpose of this study was to explore the coping strategies of adolescents with divorced parents. Methods: This study used the Narrative Review method. Literature review through Ebsco, Pubmed, Science Direct, Sage Journals, and Google Scholar databases. The keywords used in English are "coping skills OR coping behavior OR coping strategies" AND "adolescent OR adolescence OR young adult OR teenager" AND "divorce OR divorced OR divorces OR parental divorce" with full text, free access, research article, review article, in English and Indonesian, population and sample of adolescents aged 11-24 years with parental divorce, and the publication period of the last 10 years (2013-2022). Results: We found 10 articles with different coping strategies. There are 9 articles with adaptive (positive) coping strategies, while 1 article covering both adaptive and maladaptive (negative) coping strategies. As for the use of problem-focused coping 4 articles, the use of emotion-focused coping 3 articles and using both problem-focused coping and emotion-focused coping 3 articles. Conclusion: There are differences in coping strategies in each research area including problem-focused coping, emotion-focused coping, or both in the adaptive and maladaptive categories.